The Concept of Peace in The Bible and The Qur’an: A Comparative Study - Rashid, Ungaran; Din, Fadzilah; Muhamad Syukri, Abdul Salam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This article examines the concept of peace from the perspective of the Bible and the Qur’an, in this respect, the researchers see some similarities and diversities instead of from Islamic or Christian traditions. Analytical study of the Bible and the Qur’an, especially from contemporary commentators, and comparative approaches are conducted as the methodology of the study in this article. The purpose of this article is to study whether the topic can be applied to build a harmonious life between Christian community and Muslim community or not, especially in the situation of conflict in both communities. Besides, the research is hoped to produce a fruitful discussion between Christian and Muslim scholars. As a result of this research, the researchers have discovered an important finding, namely, the concept of peace found both in the Bible and the Qur’an relates to some aspects of life such as to be good, righteous, and introspective.